2020
DOI: 10.3389/fonc.2020.01014
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition in Patients With Hypothalamic-Pituitary Tumors

Abstract: Objectives: The current study aimed to investigate whether childhood-onset craniopharyngioma patients are impaired in social-cognitive skills, and whether individual differences in task performance are modulated by the neurohormone oxytocin. Study design: We tested 31 adamantinomatous craniopharyngioma patients with and without hypothalamic lesions and 35 age-and gender-matched healthy controls. To test for between-group differences in social-cognitive skills, we experimentally assessed participants' abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Consistent with our findings, previous studies also have shown higher depression scores in those with severe forms of “common” obesity (BMI > 99th percentile) compared to children with BMI 85th-99th percentile ( 36 ). Prior studies also identified impairments in social cognition in survivors of childhood craniopharyngioma, including difficulties correctly interpreting tone of voice and others’ mental states that may underlie our findings ( 38 41 ). Given the importance of social relationships to youth mental health, these findings are highly concerning for this already at-risk population and worthy of additional investigation for factors impacting social functioning and opportunities to intervene ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with our findings, previous studies also have shown higher depression scores in those with severe forms of “common” obesity (BMI > 99th percentile) compared to children with BMI 85th-99th percentile ( 36 ). Prior studies also identified impairments in social cognition in survivors of childhood craniopharyngioma, including difficulties correctly interpreting tone of voice and others’ mental states that may underlie our findings ( 38 41 ). Given the importance of social relationships to youth mental health, these findings are highly concerning for this already at-risk population and worthy of additional investigation for factors impacting social functioning and opportunities to intervene ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 54%
“…A recent study showed that paediatric-onset craniopharyngioma patients with hypothalamic lesions were less able to identify the correct emotional content of vocal expressions and to infer others’ thoughts, feelings and intentions compared to healthy controls. 55 However, there is still no evidence for a possible role of the hypocretinergic system in developing these cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, decreased salivary concentrations of basal and/or stimulated oxytocin have been observed in craniopharyngioma patients 82,[122][123][124] when compared with healthy controls. Reduced oxytocin levels were associated with anxiety 125 and worse social cognition 126 .…”
Section: Hypopituitarismmentioning
confidence: 98%
“…Craniopharyngioma patients may suffer from behavioral, psychosocial or psychiatric disorders, such as anxiety, impulse-control disorders, depression, apathy 124,[128][129][130] or severe food craving behaviors requiring additional specific psychiatric and/or psychosocial support. Pharmacotherapeutic interventions with central stimulating agents, such as dextroamphetamines may help to decrease daytime sleepiness and increase concentration and may be considered to target psychosocial symptoms.…”
Section: Psychosocial Disordersmentioning
confidence: 99%